Running-In Behavior of Wet Multi-plate Clutches: Introduction of a New Test Method for Investigation and Characterization - Voelkel, Katharina; Pflaum, Hermann; Stahl, Karsten (Chinese Journal of Mechanical Engineering, 2020)
Wet multi-plate clutches are relevant components of modern drivetrain applications, not only in terms of function but also safety and comfort. Especially at the beginning of their lifetime, distinct changes of the friction behavior may occur and make the actuation of the clutch challenging. This transcript describes the typical running-in behavior of wet multi-plate clutches and gives a general definition for running-in of clutches. Moreover, a new test method to systematically investigate the running-in behavior of clutches is introduced. This test method contains a test procedure to characterize the running-in behavior on different load levels. Furthermore, a multi-stage procedure to evaluate and characterize the running-in behavior of clutches with mathematical approaches and new characteristic values is given. The quality of the test method is demonstrated on the example of three different tribological systems from dual clutch transmissions (DCT) and automatic transmissions (AT) application using paper friction linings.
CRIS-Team Scopus Importer:2025-05-19
Keywords: Clutch; Paper friction lining; Running-in; Test method